A silica sol shell and its preparation method

By adding carbon fiber to the silicon sol shell and using a combination process of multi-layer coating and sand, the problem of low high temperature breathability of the silicon sol shell is solved, and a low thickness, high strength and high breathability shell is achieved, reducing the The pinhole defects of the castings and improve the product's pass rate.

CN115401163BActive Publication Date: 2025-02-25HEBEI GANGYAN DEKAI TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211071776.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-31
Publication Date
2025-02-25
Estimated Expiration
2042-08-31

AI Technical Summary

Technical Problem

The high-temperature breathability of the silicon sol shell is low, resulting in pinhole defects often inside the castings, affecting product pass rate and casting costs.

Method used

By adding carbon fiber to the mold shell and using a combination process of multiple layers of coating and sand, including surface layer, transition layer, reinforcement layer and sealing layer, the components and ratio of each layer are controlled to reduce the mold shell thickness. Improve its strength and porosity.

Benefits of technology

The silicon sol shell has achieved the characteristics of low thickness, high strength, large porosity and good breathability, which reduces the defects of the pinhole of the castings and improves the metallurgical quality and pass rate of the castings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115401163B_ABST
    Figure CN115401163B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of investment casting, and in particular to a silica sol mold shell and a preparation method thereof. The preparation method of the silica sol mold shell of the present invention comprises: the mold group is sequentially subjected to the steps of dip coating of a surface layer, sprinkling of a surface layer sand, dip coating of a transition layer, sprinkling of a transition layer sand, dip coating of a reinforcement layer, sprinkling of a reinforcement layer sand and dip coating of a sealing layer to obtain a mold shell; the mold shell is dewaxed and roasted to obtain the silica sol mold shell; wherein the transition layer coating comprises, by weight, 800 to 1000 parts of mullite powder, 0.8 to 1.2 parts of carbon fiber and 480 to 520 parts of silica sol; the reinforcement layer coating comprises, by weight, 1400 to 1800 parts of mullite powder, 0.8 to 1.2 parts of carbon fiber and 480 to 520 parts of silica sol. The method can reduce the thickness of the mold shell while maintaining its strength and increase the air permeability of the mold shell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of investment casting, in particular to a silica sol shell and a preparation method thereof. Background Art

[0002] Investment casting is an advanced process of near-net-shape forming, which is mostly used to realize the molding of complex, precise, thin-walled castings. The products can be used directly without or with little processing. It is widely used in industrial fields such as aircraft engines, and the jewelry industry also widely adopts investment casting technology. The modern investment casting process mainly includes: pressing wax molds, mold assembly, mold shell preparation, smelting and pouring, shell cleaning and cutting, heat treatment and non-destructive and dimensional inspection. Among them, the mold shell preparation process is particularly important. A high-quality mold shell can obtain casting products with smooth surface, clear edges and corners, correct size and good quality. Air permeability is an important indicator of high-quality mold shells, and the air permeability of mold shells mainly depends on the density of their structure.

[0003] Silica sol shells have the advantages of simple process, good coating stability, strong high temperature deformation resistance, good product surface quality and no air pollution during shell making. Today, with increasingly stringent product quality and environmental protection requirements, the application of this type of shell is on the rise. However, the high temperature air permeability of silica sol shells is low. Limited by the existing shell preparation process, there are usually pinhole defects of varying degrees inside the castings. Some thin-walled, blade-type and airtight castings are judged to be scrapped if they have pinhole defects above level 2, and the product qualification rate is low, which increases the casting cost. In order to avoid pinhole defects, general structural parts will add additional cold iron and exhaust measures, resulting in complex mold assembly process and low production rate. In order to avoid pinhole defects in products, the main methods currently used are to improve the smelting quality of molten metal and reduce the number of shell layers, but the effect is microscopic, and reducing the number of shell layers will cause problems such as insufficient shell strength and pouring fire.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The first object of the present invention is to provide a method for preparing a silica sol shell, which can reduce the thickness of the shell while maintaining its strength, increase the porosity of the shell, and improve the air permeability, thereby facilitating exhaust.

[0006] The second object of the present invention is to provide a silica sol mold shell, which has the characteristics of low thickness, high strength, large porosity and good air permeability. When used in investment casting, it can reduce pinhole defects in castings and improve the metallurgical quality and pass rate of castings.

[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0008] The present invention provides a method for preparing a silica sol mold shell, comprising: sequentially subjecting a mold assembly to dip coating of a surface layer, sprinkling of surface layer sand, dip coating of a transition layer, sprinkling of transition layer sand, dip coating of a reinforcement layer, sprinkling of reinforcement layer sand, and dip coating of a sealing layer to obtain a mold shell; the mold shell is dewaxed and calcined to obtain the silica sol mold shell;

[0009] The transition layer coating comprises, by weight, 800 to 1000 parts of mullite powder, 0.8 to 1.2 parts of carbon fiber and 480 to 520 parts of silica sol;

[0010] The reinforcement layer coating comprises, by weight, 1400-1800 parts of mullite powder, 0.8-1.2 parts of carbon fiber and 480-520 parts of silica sol.

[0011] Furthermore, the surface coating comprises, by weight, 19 to 21 parts of zircon powder, 6 to 8 parts of defoaming agent, 8 to 10 parts of wetting agent and 4.5 to 5.5 parts of silica sol.

[0012] Preferably, the particle size of the zircon powder is 300-350 mesh.

[0013] Preferably, the surface layer sand comprises corundum sand.

[0014] Preferably, the particle size of the surface sand is 80-120 meshes.

[0015] Furthermore, in the transition layer coating, the particle size of the mullite powder is 180-220 meshes.

[0016] Preferably, the transition layer sand comprises mullite sand.

[0017] Preferably, the particle size of the transition layer sand is 50-70 mesh.

[0018] Furthermore, in the reinforcement layer coating, the particle size of the mullite powder is 180-220 meshes.

[0019] Preferably, the reinforcement layer sand comprises mullite sand.

[0020] Preferably, the particle size of the reinforcement layer sand is 25 to 35 meshes.

[0021] Furthermore, the carbon fiber includes carbon fiber for precision casting.

[0022] Preferably, the diameter of the carbon fiber is 15-25 μm, and the length of the carbon fiber is 0.8-1.2 mm.

[0023] Furthermore, the sealing layer coating includes mullite powder and silica sol.

[0024] Preferably, the mass ratio of the mullite powder to the silica sol is 5 to 9:5.

[0025] Preferably, in the sealing layer coating, the particle size of the mullite powder is 180-220 meshes.

[0026] Furthermore, the calcination temperature is 800-850° C., and the calcination time is 2-4 hours.

[0027] Preferably, the calcination comprises: heating to 800-850°C at a rate of ≤200°C / h, maintaining the temperature for 2-4h, and cooling the furnace to below 200°C.

[0028] Furthermore, the method for preparing the silica sol shell comprises the following steps:

[0029] (A) Dipping the mold into a surface coating, sprinkling surface sand, and drying to obtain a surface shell;

[0030] (B) the surface shell is dipped in transition layer coating, sprinkled with transition layer sand and dried to obtain a transition layer shell;

[0031] (C) After the transition layer shell is dipped in the reinforcement layer coating, sprinkled with reinforcement layer sand and dried, the steps of dipping in the reinforcement layer coating, sprinkling with reinforcement layer sand and drying are repeated once to obtain a reinforcement layer shell;

[0032] (D) the reinforcement layer mold shell is dip-coated with a sealing layer coating to obtain a mold shell;

[0033] (E) The shell mold in step (D) is dewaxed and calcined to obtain the silica sol shell mold.

[0034] The present invention also provides a silica sol shell, which is prepared by the method for preparing the silica sol shell as described above.

[0035] Furthermore, the thickness of the silica sol shell is 4 to 4.2 mm.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The preparation method of the silica sol shell of the present invention can reduce the thickness of the shell while maintaining its strength by adding carbon fiber to the shell and using appropriate components and their proportions in each layer, and also increase the porosity of the shell, improve the air permeability, and facilitate exhaust.

[0038] The silica sol shell prepared by the preparation method of the silica sol shell of the present invention can have the characteristics of low thickness, large porosity, good air permeability, high high-temperature strength and good yieldability; after pouring the silica sol shell prepared by the present invention, a casting product with smooth surface, clear edges and corners, correct size and good quality can be obtained, which improves the qualification rate of castings, especially some thin-walled castings, blade-type castings and castings with airtightness requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0040] Figure 1 It is a schematic diagram of the process of preparing the silica sol shell of the present invention.

[0041] Figure 2 It is a schematic diagram of mullite powder and carbon fiber in the silica sol shell of the present invention.

[0042] Figure 3 This is a thickness test diagram of the silica sol shell of Example 1 of the present invention and the silica sol shell of Comparative Example 1.

[0043] Figure 4 This is a fluorescence detection image of a casting obtained by pouring the silica sol shell of Example 1 of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] 1- Mullite powder; 2- Carbon fiber. DETAILED DESCRIPTION

[0046] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0047] A silica sol shell and a preparation method thereof according to an embodiment of the present invention are described in detail below.

[0048] See also Figure 1 In some embodiments of the present invention, a method for preparing a silica sol mold shell is provided, comprising: applying a surface layer coating, sprinkling a surface layer sand, applying a transition layer coating, sprinkling a transition layer sand, applying a reinforcement layer coating, sprinkling a reinforcement layer sand, and applying a sealing layer coating to a mold shell; the mold shell is dewaxed and calcined to obtain a silica sol mold shell;

[0049] The transition layer coating comprises, by weight, 800 to 1000 parts of mullite powder, 0.8 to 1.2 parts of carbon fiber and 480 to 520 parts of silica sol;

[0050] The reinforcement layer coating comprises, by weight, 1400-1800 parts of mullite powder, 0.8-1.2 parts of carbon fiber and 480-520 parts of silica sol.

[0051] The preparation method of the silica sol shell of the present invention adds carbon fiber to the silica sol shell, so that the silica sol shell can maintain its strength while reducing the shell thickness, increase the porosity, improve the air permeability, and facilitate exhaust.

[0052] In some embodiments of the present invention, in the transition layer coating, typically but not limiting, for example, the weight proportion of mullite powder can be 800 parts, 810 parts, 820 parts, 830 parts, 840 parts, 850 parts, 860 parts, 870 parts, 880 parts, 890 parts, 900 parts, 910 parts, 920 parts, 930 parts, 940 parts, 950 parts, 960 parts, 970 parts, 980 parts, 990 parts or 1000 parts, etc.; the weight proportion of carbon fiber can be 0.8 parts, 0.9 parts, 1 parts, 1.1 parts or 1.2 parts, etc.; the weight proportion of silica sol can be 480 parts, 490 parts, 500 parts, 510 parts and 520 parts, etc.

[0053] In some embodiments of the present invention, in the reinforcement layer coating, typically but not limiting, for example, the weight proportion of mullite powder can be 1400 parts, 1450 parts, 1500 parts, 1550 parts, 1600 parts, 1650 parts, 1700 parts, 1750 parts or 1800 parts, etc.; the weight proportion of carbon fiber can be 0.8 parts, 0.9 parts, 1 parts, 1.1 parts or 1.2 parts; the weight proportion of silica sol can be 480 parts, 490 parts, 500 parts, 510 parts or 520 parts.

[0054] In some embodiments of the present invention, the surface coating comprises, by weight: 19 to 21 parts of zircon powder, 6 to 8 parts of defoaming agent, 8 to 10 parts of wetting agent and 4.5 to 5.5 parts of silica sol.

[0055] In some specific embodiments of the present invention, the surface coating comprises, by weight: 19 to 21 parts of zircon powder, 6 to 8 parts of defoaming agent, 8 to 10 parts of wetting agent and 5 parts of silica sol.

[0056] In some embodiments of the present invention, the particle size of the zircon powder is 300-350 mesh; preferably, the particle size of the zircon powder is 320 mesh; more preferably, the content of ZrO2 in the zircon powder is ≥65wt%.

[0057] In some embodiments of the present invention, the content of SiO2 in the silica sol is 29wt% to 31wt%, the content of Na2O is ≤0.5wt%, and the pH of the silica sol is 9.5 to 10.5. The silica sol in each layer of the coating of the silica sol shell of the present invention adopts the above silica sol.

[0058] In some embodiments of the present invention, the defoaming agent includes an organosilicon defoaming agent and / or a polyether defoaming agent.

[0059] In some embodiments of the present invention, the wetting agent includes WET-10T wetting agent and / or WET-10S wetting agent.

[0060] In some embodiments of the present invention, a method for preparing a surface coating comprises: mixing zircon powder, a defoamer, a wetting agent and silica sol to obtain the surface coating; preferably, the mixing comprises stirring at a speed of 22 to 50 r / min.

[0061] In some embodiments of the present invention, the surface sand comprises corundum sand; preferably, the content of Al2O3 in the corundum sand is ≥98.5wt%.

[0062] In some embodiments of the present invention, the particle size of the surface sand is 80-120 meshes; preferably, the particle size of the surface sand is 100 meshes.

[0063] In some embodiments of the present invention, the transition layer coating comprises, by weight, 800 to 1000 parts of mullite powder, 0.8 to 1.2 parts of carbon fiber and 500 parts of silica sol.

[0064] In some embodiments of the present invention, in the transition layer coating, the particle size of the mullite powder is 180-220 meshes; preferably, the particle size of the mullite powder is 200 meshes.

[0065] In some embodiments of the present invention, a method for preparing a transition layer coating comprises: mixing mullite powder, carbon fiber and silica sol to obtain a transition layer coating; preferably, the mixing comprises stirring at a speed of 22 to 50 r / min.

[0066] In some embodiments of the present invention, the transition layer sand comprises mullite sand; preferably, the particle size of the transition layer sand is 50-70 mesh; more preferably, the particle size of the transition layer sand is 60 mesh.

[0067] In some embodiments of the present invention, the reinforcement layer coating comprises, by weight: 1400-1800 parts of mullite powder, 0.8-1.2 parts of carbon fiber and 500 parts of silica sol.

[0068] In some embodiments of the present invention, in the reinforcement layer coating, the particle size of the mullite powder is 180-220 meshes; preferably, the particle size of the mullite powder is 200 meshes.

[0069] In some embodiments of the present invention, a method for preparing a reinforcement layer coating comprises: mixing mullite powder, carbon fiber and silica sol to obtain a reinforcement layer coating; preferably, mixing comprises stirring at a speed of 22 to 50 r / min.

[0070] In some embodiments of the present invention, the reinforcement layer sand comprises mullite sand; preferably, the particle size of the reinforcement layer sand is 25-35 meshes; more preferably, the particle size of the reinforcement layer sand is 30 meshes.

[0071] In some embodiments of the present invention, the carbon fiber includes precision casting carbon fiber; preferably, the diameter of the carbon fiber is 15-25 μm, and the length of the carbon fiber is 0.8-1.2 mm; more preferably, the diameter of the carbon fiber is 20 μm, and the length of the carbon fiber is 1 mm. The carbon fiber in the transition layer coating and the reinforcement layer coating of the present invention both adopts the above-mentioned carbon fiber.

[0072] In some embodiments of the present invention, the sealing layer coating includes mullite powder and silica sol; preferably, the mass ratio of mullite powder to silica sol is 5 to 9:5; typically but not limitatively, for example, the mass ratio of mullite powder to silica sol is 5:5, 6:5, 7:5, 8:5 or 9:5, etc.

[0073] In some embodiments of the present invention, in the sealing layer coating, the particle size of the mullite powder is 180-220 meshes; preferably, the particle size of the mullite powder is 200 meshes.

[0074] In some embodiments of the present invention, a method for preparing a sealing layer coating comprises: mixing mullite powder and silica sol to obtain a sealing layer coating; preferably, the mixing comprises stirring at a speed of 22 to 50 r / min.

[0075] In the preparation method of the silica sol mold shell of the present invention, each layer of the mold shell adopts appropriate raw materials and their proportions, so that the thickness of the mold shell can be reduced while maintaining its strength, reducing the amount of refractory materials used, which is beneficial to environmental protection; at the same time, the porosity of the mold shell can be increased, which is beneficial to exhaust, improves the metallurgical quality of the product, reduces pinhole defects in castings, and effectively improves the qualified rate of the product.

[0076] In some embodiments of the present invention, the calcination temperature is 800-850°C, and the calcination time is 2-4h; typically but not limitatively, for example, the calcination temperature is 800°C, 805°C, 810°C, 815°C, 820°C, 825°C, 830°C, 835°C, 840°C, 845°C or 850°C, etc.; the calcination time is 2h, 2.5h, 3h, 3.5h or 4h, etc.

[0077] In some embodiments of the present invention, the calcination comprises: heating to 800-850°C at a rate of ≤200°C / h, maintaining the temperature for 2-4h, and cooling the furnace to below 200°C.

[0078] In some specific embodiments of the present invention, the calcination temperature is 810-850°C.

[0079] In some specific embodiments of the present invention, the oxygen content during the calcination process is 19% to 23%.

[0080] In some embodiments of the present invention, the method for preparing the silica sol shell comprises the following steps:

[0081] (A) Dipping the mold into a surface coating, sprinkling surface sand, and drying to obtain a surface shell;

[0082] (B) the surface shell is dipped in transition layer coating, sprinkled with transition layer sand and dried to obtain a transition layer shell;

[0083] (C) After the transition layer shell is dipped in the reinforcement layer coating, sprinkled with reinforcement layer sand and dried, the steps of dipping in the reinforcement layer coating, sprinkling with reinforcement layer sand and drying are repeated once to obtain a reinforcement layer shell;

[0084] (D) the reinforcement layer shell is dip-coated with the sealing layer coating to obtain the shell;

[0085] (E) The mold shell in step (D) is dewaxed and calcined to obtain a silica sol mold shell.

[0086] In some embodiments of the present invention, in step (A), the method for preparing the module includes: using SL996 medium-temperature wax mold to prepare a wax mold, a runner, a sprue and a pouring cup that are consistent with the shape of the casting and meet the dimensional tolerance requirements, and then combining them in a group-of-one manner to obtain the module; preferably, the preparation includes using a model IP62 double-station wax press and a 7075 aluminum alloy mold.

[0087] In some embodiments of the present invention, in step (A), the module is slowly immersed in the surface coating to obtain a module whose surface is sufficiently and evenly coated with a layer of surface coating, and then the surface layer shell is obtained after being sprinkled with surface sand and dried; preferably, sprinkling the surface sand includes evenly covering the entire surface of the module coated with the surface coating with a layer of surface sand.

[0088] In some embodiments of the present invention, in step (B), the surface layer mold shell is slowly immersed in the transition layer coating to obtain a module whose surface is sufficiently and evenly coated with a layer of transition layer coating; then, the transition layer mold shell is obtained after being sprinkled with transition layer sand and dried; preferably, sprinkling the transition layer sand includes evenly covering the entire surface of the module coated with the transition layer coating with a layer of transition layer sand.

[0089] In some embodiments of the present invention, in step (B), the surface shell is immersed in the transition layer coating for the first dipping, and the material is controlled after completion. After 20 seconds of controlling the material, it is immersed in the transition layer coating for the second dipping to obtain a module whose surface is fully and evenly coated with a layer of transition layer coating.

[0090] In some embodiments of the present invention, in step (C), the transition layer mold shell is immersed in the reinforcement layer coating to obtain a module whose surface is sufficiently and evenly coated with a layer of the reinforcement layer coating, and then the reinforcement layer sand is sprinkled; the above operation is then repeated once to obtain the reinforcement layer mold shell; preferably, sprinkling the reinforcement layer sand includes evenly covering the entire surface of the module coated with the reinforcement layer coating with a layer of reinforcement layer sand.

[0091] In some embodiments of the present invention, in step (C), the transition layer shell is immersed in the reinforcement layer coating for the first dipping, and the material is controlled after completion. After 20 seconds of control, it is immersed in the reinforcement layer coating for the second dipping to obtain a module whose surface is fully and evenly coated with a layer of reinforcement layer coating.

[0092] In some embodiments of the present invention, in step (D), after the floating sand of the reinforcement layer shell is cleaned, it is immersed in a sealing layer coating to obtain a module with a surface sufficiently and evenly coated with a layer of sealing layer coating, and then dried to obtain a shell.

[0093] In some embodiments of the present invention, during the process of dipping each layer of coating, accumulation of material and sagging are strictly prohibited. After dipping, if there is leakage or accumulation in deep holes, manual filling is required.

[0094] In some embodiments of the present invention, in step (E), the dewaxing temperature is 163-173° C., and the dewaxing pressure is 0.7-0.8 MPa.

[0095] In some embodiments of the present invention, a silica sol-type shell is also provided, which is prepared by the above-mentioned method for preparing the silica sol-type shell.

[0096] In some embodiments of the present invention, the thickness of the silica sol shell is 4 to 4.2 mm.

[0097] See also Figure 2 In some embodiments of the present invention, the silica sol shell includes mullite powder 1 and carbon fiber 2.

[0098] In some embodiments of the present invention, the silica sol mold shell includes 1 surface layer, 1 transition layer, 2 reinforcement layers and 1 sealing layer; that is, the silica sol mold shell includes 1 surface layer coating layer, 1 surface layer sand layer, 1 transition layer coating layer, 1 transition layer sand layer, 2 reinforcement layer coating layers, 2 reinforcement layer sand layers and 1 sealing layer coating layer.

[0099] The silica sol shell of the present invention has the characteristics of low thickness, good air permeability, high high-temperature strength and good yieldability. After casting, a casting product with a smooth surface, clear edges and corners, correct size and good quality can be obtained by using the silica sol shell prepared by the present invention, which reduces the work of subsequent product grinding and defect removal, can greatly reduce the work intensity of on-site workers, and improve work efficiency; and the silica sol shell of the present invention has a wide range of applications and can meet the casting of most alloys such as Al, Mg and other precision products; the process is simple, and the process flow is easy to form batch operations, thereby improving production efficiency.

[0100] Example 1

[0101] The method for preparing the silica sol shell provided in this embodiment comprises the following steps:

[0102] (1) A wax mold, runner, nozzle, and pouring cup that are consistent with the shape of the casting and meet the dimensional tolerance requirements are prepared using a model IP62 double-station wax press, SL996 medium-temperature wax, and a 7075 aluminum alloy mold. The mold is then assembled in a one-piece manner.

[0103] (2) Add 20 parts of 320 mesh zircon powder (ZrO2 ≥ 65wt%), 7 parts of silicone defoamer, 9 parts of WET-10S wetting agent and 5 parts of silica sol (SiO2 is 30wt% ± 1wt%, Na2O ≤ 0.5wt%, pH is 9.5-10.5) into a stirring barrel, stir at 22-50r / min, and mix well to obtain the surface coating.

[0104] (3) Slowly immerse the module into the surface coating at an angle of 30°±2°, rotate it slightly, and use a brush to eliminate the air trapped in the grooves and corners of the module so that it is evenly coated with a layer of surface coating. It is strictly forbidden to have material accumulation and sagging. After completion, control the material. After 20s of control, immerse it in the surface coating again for a second immersion; then extend the module with the surface coating into the sand spraying machine, and rotate it up and down and left and right to make the entire surface of the module evenly covered with a layer of 100 mesh corundum sand (Al2O3≥98.5wt%), and then hang it on a rack for drying to obtain a surface shell.

[0105] (4) Add 900 parts of 200-mesh mullite powder, 1 part of precision casting carbon fiber (diameter 20 μm, length 1 mm) and 500 parts of silica sol (SiO2 is 30 wt% ± 1 wt%, Na2O ≤ 0.5 wt%, pH 9.5-10.5) into a stirring barrel, stir at 22-50 r / min, and mix well to obtain a transition layer coating.

[0106] (5) Immerse the surface shell in the transition layer coating for the first immersion, and then control the material. After 20 seconds of control, immerse it in the transition layer coating for the second immersion to obtain a module with a layer of transition layer coating on the surface fully and evenly coated; extend the module coated with the transition layer coating into a sand spraying machine, and rotate it up and down and left and right to make the entire surface of the module evenly covered with a layer of 60 mesh mullite sand, and then hang it on a rack for drying to obtain a transition layer shell.

[0107] (6) Add 1600 parts of 200-mesh mullite powder, 1 part of precision casting carbon fiber (diameter 20 μm, length 1 mm) and 500 parts of silica sol (SiO2 is 30wt%±1wt%, Na2O≤0.5wt%, pH is 9.5-10.5) into a stirring barrel, stir at 22-50 r / min, and mix well to obtain a reinforcement layer coating.

[0108] (7) Immerse the transition layer shell in the reinforcement layer coating for the first immersion, and then control the material. After controlling the material for 20 seconds, immerse it in the reinforcement layer coating for the second immersion to obtain a module with a layer of reinforcement layer coating fully and evenly coated on the surface; extend the module coated with the reinforcement coating into a sand spraying machine, and rotate it up and down and left and right to make the entire surface of the module evenly covered with a layer of 30 mesh mullite sand, and then hang it on a rack for drying.

[0109] (8) Repeat step (7) once to obtain a reinforced shell.

[0110] (9) Add 200-mesh mullite powder and silica sol (SiO2 is 30wt%±1wt%, Na2O≤0.5wt%, pH is 9.5-10.5) in a mass ratio of 7:5 into a stirring barrel, stir at 22-50r / min, and mix well to obtain a sealing layer coating.

[0111] (10) After using compressed air to remove the floating sand from the reinforcement shell, slowly immerse it in the surface coating at an angle of 30°±2°, rotate it slightly, and use a brush to eliminate the air trapped in the grooves and corners of the module so that it is evenly coated with a layer of sealing coating. It is strictly forbidden to have material accumulation or sagging; then hang it on a rack to dry to obtain the shell.

[0112] (11) Remove the excess mold shell from the pouring cup edge of the mold shell in step (10) and make a hole with a size of The wax discharge hole is opened; then the product is quickly transferred to the steam dewaxing kettle, the machine door is closed, the steam valve is opened, the pressure reaches 0.6MPa within 10s, and the temperature reaches 160℃, and dewaxing is started.

[0113] (12) The dewaxed shell mold is heated to 800°C at a rate of 200°C / h and kept in a heat treatment for 4 hours. The oxygen content during the heat treatment is 19% to 23%. The furnace is cooled to below 200°C to obtain a silica sol shell mold.

[0114] Example 2

[0115] The preparation method of the silica sol shell provided in this embodiment is similar to that in Example 1, except that:

[0116] In step (2), 19 parts of 320 mesh zircon powder (ZrO2≥65wt%), 6 parts of silicone defoamer, 8 parts of WET-10S wetting agent and 5 parts of silica sol (SiO2 is 30wt%±1wt%, Na2O≤0.5wt%, pH is 9.5-10.5) are added to a stirring barrel, stirred at 22-50r / min, and mixed evenly to obtain a surface coating.

[0117] In step (4), 800 parts of 200-mesh mullite powder, 1 part of precision casting carbon fiber (diameter 20 μm, length 1 mm) and 500 parts of silica sol (SiO2 is 30wt%±1wt%, Na2O≤0.5wt%, pH is 9.5-10.5) are added to a stirring barrel, stirred at 22-50 r / min, and mixed evenly to obtain a transition layer coating.

[0118] In step (6), 1800 parts of 200 mesh mullite powder, 1 part of carbon fiber for precision casting (diameter 20 μm, length 1 mm) and 500 parts of silica sol (SiO2 is 30wt% ± 1wt%, Na2O ≤ 0.5wt%, pH is 9.5-10.5) are added to a stirring barrel, stirred at 22-50 r / min, and mixed evenly to obtain a reinforcement layer coating.

[0119] In step (9), the mass ratio of mullite powder to silica sol is 5:5.

[0120] Example 3

[0121] The preparation method of the silica sol shell provided in this embodiment is similar to that in Example 1, except that:

[0122] In step (2), 21 parts of 320 mesh zircon powder (ZrO2≥65wt%), 8 parts of silicone defoamer, 10 parts of WET-10S wetting agent and 5 parts of silica sol (SiO2 is 30wt%±1wt%, Na2O≤0.5wt%, pH is 9.5-10.5) are added to a stirring barrel, stirred at 22-50r / min, and mixed evenly to obtain a surface coating.

[0123] In step (4), 1000 parts of 200-mesh mullite powder, 1 part of precision casting carbon fiber (diameter 20 μm, length 1 mm) and 500 parts of silica sol (SiO2 is 30wt%±1wt%, Na2O≤0.5wt%, pH is 9.5-10.5) are added to a stirring barrel, stirred at 22-50 r / min, and mixed evenly to obtain a transition layer coating.

[0124] In step (6), 1400 parts of 200 mesh mullite powder, 1 part of carbon fiber for precision casting (diameter 20 μm, length 1 mm) and 500 parts of silica sol (SiO2 is 30wt% ± 1wt%, Na2O ≤ 0.5wt%, pH is 9.5-10.5) are added to a stirring barrel, stirred at 22-50 r / min, and mixed evenly to obtain a reinforcement layer coating.

[0125] In step (9), the mass ratio of mullite powder to silica sol is 9:5.

[0126] Comparative Example 1

[0127] The preparation method of the silica sol shell provided in this comparative example comprises the following steps:

[0128] (1) A wax mold, runner, nozzle, and pouring cup that are consistent with the shape of the casting and meet the dimensional tolerance requirements are prepared using a model IP62 double-station wax press, SL996 medium-temperature wax, and a 7075 aluminum alloy mold. The mold is then assembled in a one-piece manner.

[0129] (2) Add 20 parts of 320 mesh zircon powder (ZrO2 ≥ 65wt%), 7 parts of silicone defoamer, 9 parts of WET-10S wetting agent and 5 parts of silica sol (SiO2 is 30wt% ± 1wt%, Na2O ≤ 0.5wt%, pH is 9.5-10.5) into a stirring barrel, stir at 22-50r / min, and mix well to obtain the surface coating.

[0130] (3) Slowly immerse the module into the surface coating at an angle of 30°±2°, rotate it slightly, and use a brush to eliminate the air trapped in the grooves and corners of the module so that it is evenly coated with a layer of surface coating. It is strictly forbidden to have material accumulation and sagging. After completion, control the material. After 20s of control, immerse it in the surface coating again for a second immersion; then extend the module with the surface coating into the sand spraying machine, and rotate it up and down and left and right to make the entire surface of the module evenly covered with a layer of 100 mesh corundum sand (Al2O3≥98.5wt%), and then hang it on a rack for drying to obtain a surface shell.

[0131] (4) Add 900 parts of 200-mesh mullite powder and 500 parts of silica sol (SiO2 is 30wt%±1wt%, Na2O≤0.5wt%, pH is 9.5-10.5) into a stirring barrel, stir at 22-50r / min, and mix well to obtain a transition layer coating.

[0132] (5) Immerse the surface shell in the transition layer coating for the first immersion, and then control the material. After 20 seconds of control, immerse it in the transition layer coating for the second immersion to obtain a module with a layer of transition layer coating on the surface fully and evenly coated; extend the module coated with the transition layer coating into a sand spraying machine, and rotate it up and down and left and right to make the entire surface of the module evenly covered with a layer of 60 mesh mullite sand, and then hang it on a rack for drying to obtain a transition layer shell.

[0133] (6) Add 1600 parts of 200-mesh mullite powder and 500 parts of silica sol (SiO2 is 30wt%±1wt%, Na2O≤0.5wt%, pH is 9.5-10.5) into a stirring barrel, stir at 22-50r / min, and mix well to obtain a reinforcement layer coating.

[0134] (7) Immerse the transition layer shell in the reinforcement layer coating for the first immersion, and then control the material. After controlling the material for 20 seconds, immerse it in the reinforcement layer coating for the second immersion to obtain a module with a layer of reinforcement layer coating fully and evenly coated on the surface; extend the module coated with the reinforcement coating into a sand spraying machine, and rotate it up and down and left and right to make the entire surface of the module evenly covered with a layer of 30 mesh mullite sand, and then hang it on a rack for drying.

[0135] (8) Repeat step (7) twice to obtain a reinforced shell.

[0136] (9) Add 200-mesh mullite powder and silica sol (SiO2 is 30wt%±1wt%, Na2O≤0.5wt%, pH is 9.5-10.5) in a mass ratio of 7:5 into a stirring barrel, stir at 22-50r / min, and mix well to obtain a sealing layer coating.

[0137] (10) After using compressed air to remove the floating sand from the reinforcement shell, slowly immerse it in the surface coating at an angle of 30°±2°, rotate it slightly, and use a brush to eliminate the air trapped in the grooves and corners of the module so that it is evenly coated with a layer of sealing coating. It is strictly forbidden to have material accumulation or sagging; then hang it on a rack to dry to obtain the shell.

[0138] (11) Remove the excess mold shell from the pouring cup edge of the mold shell in step (10) and make a hole with a size of The wax discharge hole is opened; then the product is quickly transferred to the steam dewaxing kettle, the machine door is closed, the steam valve is opened, the pressure reaches 0.6MPa within 10s, and the temperature reaches 160℃, and dewaxing is started.

[0139] (12) The dewaxed shell mold is heated to 800°C at a rate of 200°C / h and kept in a heat treatment for 4 hours. The oxygen content during the heat treatment is 19% to 23%. The furnace is cooled to below 200°C to obtain a silica sol shell mold.

[0140] Test Example 1

[0141] The thickness of the silica sol shell of Example 1 and Comparative Example 1 was tested, and the results are as follows: Figure 3 As shown. Among them, Figure 3 Where a is the thickness of the silica sol shell in Example 1; Figure 3 Where b is the thickness of the silica sol shell of Comparative Example 1.

[0142] from Figure 3 It can be seen that the thickness of the silica sol shell of Example 1 is 4.05 mm, and the thickness of the silica sol shell of Comparative Example 1 is 5.03 mm.

[0143] The strength of the silica sol mold shells of Example 1 and Comparative Example 1 was tested by manually destroying the mold shell test.

[0144] The wet strength and dry strength of the silica sol shell of Example 1 are higher than those of the silica sol shell of Comparative Example 1.

[0145] Test Example 2

[0146] The silica sol mold shell of Example 1 was used for pouring the casting; the casting was a small thin-walled structural part, made of ZL205A, with an outer dimension of 240 mm × 120 mm × 20 mm, and a thinnest wall thickness of 3 mm; during the pouring process, the silica sol mold shell did not experience sparking or insufficient pouring, and the strength and air permeability of the silica sol mold shell met the use requirements.

[0147] After pouring, the casting is tested for fluorescence, and the results are as follows: Figure 4 shown.

[0148] from Figure 4It can be seen that the fluorescent detection of the casting surface showed no defects exceeding the standard, no pinholes, cracks and other defects, and the permeability and yieldability of the surface silica sol shell met the use requirements.

[0149] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a silica sol shell, characterized in that: include: The mold is sequentially subjected to the steps of: dipping the mold assembly in surface coating, sprinkling surface sand, dipping the mold assembly in transition coating, sprinkling transition sand, dipping the mold assembly in reinforcement coating, sprinkling reinforcement sand, and dipping the mold assembly in sealing coating to obtain a mold shell; The shell is dewaxed and calcined to obtain the silica sol shell; The surface coating comprises, by weight, 19 to 21 parts of zircon powder, 6 to 8 parts of defoaming agent, 8 to 10 parts of wetting agent and 4.5 to 5.5 parts of silica sol; The transition layer coating comprises, by weight: 800-1000 parts of mullite powder, 0.8-1.2 parts of carbon fiber and 480-520 parts of silica sol; The reinforcement layer coating comprises, by weight: 1400-1800 parts of mullite powder, 0.8-1.2 parts of carbon fiber and 480-520 parts of silica sol; The carbon fiber includes carbon fiber for precision casting, the diameter of the carbon fiber is 15 to 25 μm, and the length of the carbon fiber is 0.8 to 1.2 mm; The sealing layer coating comprises mullite powder and silica sol; The thickness of the silica sol shell is 4 to 4.2 mm.

2. The method for preparing a silica sol shell according to claim 1, characterized in that: In the surface coating, the particle size of the zircon powder is 300-350 meshes.

3. The method for preparing a silica sol shell according to claim 1, characterized in that: The surface layer sand comprises corundum sand.

4. The method for preparing a silica sol shell according to claim 3, characterized in that: The particle size of the surface sand is 80 to 120 meshes.

5. The method for preparing a silica sol shell according to claim 1, characterized in that: In the transition layer coating, the particle size of the mullite powder is 180-220 meshes.

6. The method for preparing a silica sol shell according to claim 1, characterized in that: The transition layer sand includes mullite sand.

7. The method for preparing a silica sol shell according to claim 6, characterized in that: The particle size of the transition layer sand is 50 to 70 meshes.

8. The method for preparing a silica sol shell according to claim 1, characterized in that: In the reinforcement layer coating, the particle size of the mullite powder is 180-220 meshes.

9. The method for preparing a silica sol shell according to claim 1, characterized in that: The reinforcement layer sand includes mullite sand.

10. The method for preparing a silica sol shell according to claim 9, characterized in that: The particle size of the reinforcement layer sand is 25 to 35 meshes.

11. The method for preparing a silica sol shell according to claim 1, characterized in that: In the sealing layer coating, the mass ratio of the mullite powder to the silica sol is 5 to 9:

5.

12. The method for preparing a silica sol shell according to claim 1, characterized in that: In the sealing layer coating, the particle size of the mullite powder is 180-220 meshes.

13. The method for preparing a silica sol shell according to claim 1, characterized in that: The calcination temperature is 800-850° C., and the calcination time is 2-4 hours.

14. The method for preparing a silica sol shell according to claim 13, characterized in that: The calcination comprises: heating to 800-850°C at a rate of ≤200°C / h, maintaining the temperature for 2-4h, and cooling the furnace to below 200°C.

15. The method for preparing a silica sol shell according to any one of claims 1 to 14, characterized in that: The steps include: (A) Dipping the mold into a surface coating, sprinkling surface sand, and drying to obtain a surface shell; (B) the surface layer shell is dipped in transition layer coating, sprinkled with transition layer sand and dried to obtain a transition layer shell; (C) After the transition layer shell is dipped in the reinforcement layer coating, sprinkled with reinforcement layer sand and dried, the steps of dipping in the reinforcement layer coating, sprinkling with reinforcement layer sand and drying are repeated once to obtain a reinforcement layer shell; (D) the reinforcement layer mold shell is dip-coated with a sealing layer coating to obtain a mold shell; (E) The shell mold in step (D) is dewaxed and calcined to obtain the silica sol shell mold.

16. A silica sol shell, characterized in that: The silica sol shell is prepared by the preparation method of any one of claims 1 to 15.

Citation Information

Patent Citations

  • Preparation method of fiber reinforced compound silica sol shell for investment casting

    CN103962506A

  • Preparation method of aluminum alloy casting shell

    CN111299510A